The effect of receiving antenna height on temporal fading characteristics in fixed-to-fixed radio propagation channel - Tan, K. G. (1999)
In fixed-to-fixed channel, it is widely assumed that the channel is stationary in time for above rooftop LOS propagation. This assumption is based on the fact that surrounding buildings are the main cause of multipath fading. However, the channel becomes quasi-stationary in time especially at lower receiving height (below rooftop) and for cases where moving objects are in the vicinity of receiving antenna. The effect of different receiving heights on temporal fading in terms of dynamic fading range for a fixed-to-fixed channel is addressed in this paper